The effects of temperature, slag chemistry and oxygen partial pressure on the behaviour of chromium oxide in melter slags - Bartie, Neill J. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScIng)--University of Stellenbosch, 2004.